2011
DOI: 10.1364/ol.36.001698
|View full text |Cite
|
Sign up to set email alerts
|

Precision angle sensor using an optical lever inside a Sagnac interferometer

Abstract: We built an ultra-low-noise angle sensor by combining a folded optical lever and a Sagnac interferometer. The instrument has a measured noise floor of 1.3 prad/√Hz at 2.4 kHz. We achieve this record angle sensitivity using a proof-of-concept apparatus with a conservative N=11 bounces in the optical lever. This technique could be extended to reach subpicoradian/√Hz sensitivities with an optimized design.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 7 publications
1
61
0
Order By: Relevance
“…We also demonstrated that for angular jitter, the weak-value technique for beam-deflection measurements can have much higher Fisher information than the standard technique and approach the quantum CRB in noisy environments. Considering the wide range of experiments that have now successfully employed weakvalue techniques to make high-precision measurements [1][2][3][4][5][6][7][9][10][11][12][13], this conclusion should not be too surprising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated that for angular jitter, the weak-value technique for beam-deflection measurements can have much higher Fisher information than the standard technique and approach the quantum CRB in noisy environments. Considering the wide range of experiments that have now successfully employed weakvalue techniques to make high-precision measurements [1][2][3][4][5][6][7][9][10][11][12][13], this conclusion should not be too surprising.…”
Section: Discussionmentioning
confidence: 99%
“…[1]), there are technical advantages in that these methods make the experimental approach to these limits relatively easy with common experimental equipment. Indeed, these techniques have already been successfully applied in the lab to measure with high precision the optical spin Hall effect and other polarization-dependent beam deflections [2][3][4], interferometric deflections of optical beams [5][6][7], phase shifts [8][9][10], frequency shifts [11], temperature shifts [12], and velocity measurements [13]. In most of these experiments, the weak-value-amplification (WVA) technique met and even surpassed the sensitivity of standard techniques in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we plot the SN R p X , which is defined in Eq. (8), as function of arbitrary measurement strength parameter s and preselection angle θ. From Fig.…”
Section: Schröinger Cat Statementioning
confidence: 99%
“…In recent years, postselected weak measurements have been used to great effect in metrological applications [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For a more complete overview of both the relevant theory and experiments, see the review article by Dressel et al [21].…”
Section: Introductionmentioning
confidence: 99%